Effect of Korean Red Ginseng treatment on the gene expression profile of diabetic rat retina - Yang, Hana (J Ginseng Res, 2016)
BACKGROUND: Korean Red Ginseng (KRG) is a herbal medicine used in Asian countries and is very popular for its beneficial biological properties. Diabetes mellitus (DM) and its complications are rapidly becoming a global public health concern. The literature on transcriptional changes induced by KRG in rat models of diabetic retinopathy is limited. Considering these facts, we designed this study to determine whether retinopathy-associated genes are altered in retinas of rats with DM and whether the induced changes are reversed by KRG. METHODS: Male Sprague–Dawley rats were intravenously injected with streptozotocin (50 mg/kg body weight) to induce DM, following which, KRG powder (200 mg/kg body weight) was orally administered to the KRG-treated DM rat group for 10 wks. The rats were then sacrificed, and their retinas were harvested for total RNA extraction. Microarray gene expression profiling was performed on the extracted RNA samples. RESULTS: From among > 31,000 genes investigated, the expression of 268 genes was observed to be upregulated and that of 58 genes was downregulated, with twofold altered expression levels in the DM group compared with those in the control group. Moreover, 39 genes were upregulated more than twofold and 84 genes were downregulated in the KRG-treated group compared to the DM group. The expression of the genes was significantly reversed by KRG treatment; some of these genes were analyzed further to verify the results of the microarray experiments. CONCLUSION: Taken together, our data suggest that reversed changes in the gene expression may mediate alleviating activities of KRG in rats with diabetic retinopathy.